Pelatihan Peningkatan Skill Teknisi Sepeda Motor Di Pusat Kegiatan Belajar Masyarakat - Rifaldo Pido; Mohamad Rifal; Rahmad Hidayat Boli (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Community learning activity center (PKBM) in general as an institution engaged in the world of non-formal education (PNF) with the aim of being a center for community learning activities. PKBM as a community forum for learning has many functions, especially those related to the implementation of the development of non-formal education activities. The main problem in improving the skills or skills of technicians in the maintenance and repair of motorcycles is the limited teaching resources and the importance of supporting materials or theories as well as the availability of incomplete practical support tools, as a result, when students graduate their knowledge is far behind what is needed in the world of work. Departing from obstacles or deficiencies in the community learning activity center (PKBM) Timuato Village, Kec. Blue lake district. Gorontalo, sees an opportunity to do service to help provide solutions to existing problems, namely providing training on "Training to Improve Motorcycle Technician Skills in Supporting the 2022 Job Skills Program", which is intended for PKBM students, with the aim of fostering and improving skills towards PKBM advanced, prosperous and independent.